Klosterneuburger Traditionsbuch: Registrum privilegiorum a prepositorum manu assignatorum - Baran-Szołtys, Magdalena (Brill, 2025)
The “Klosterneuburg Traditionsbuch”, which is now kept in the Augustinian canons' archive, contains over 800 records of the canonry's legal transactions, ranging from its foundation by the Babenberg Leopold III and his wife Agnes at the beginning of the 12th century to the middle of the 13th century. Das Klosterneuburger Traditionsbuch, heute im Stiftsarchiv der Augustiner Chorherren verwahrt, enthält knapp über 800 Aufzeichnungen von Rechtsgeschäften des Stiftes, die von der Gründung durch den Babenberger Leopold III. den Heiligen und seiner Frau Agnes am Beginn des 12. bis zur Mitte des 13. Jahrhunderts reichen.